Epitranscriptome in Ischemic Cardiovascular Disease: Potential Target for Therapies. Issue 6 (4th March 2022) - Quiles-Jiménez, Ana; Dahl, Tuva B.; Bjørås, Magnar; Alseth, Ingrun; Halvorsen, Bente; Gregersen, Ida
Abstract : The global risk of cardiovascular disease, including ischemic disease such as stroke, remains high, and cardiovascular disease is the cause of one-third of all deaths worldwide. The main subjacent cause, atherosclerosis, is not fully understood. To improve early diagnosis and therapeutic strategies, it is crucial to unveil the key molecular mechanisms that lead to atherosclerosis development. The field of epitranscriptomics is blossoming and quickly advancing in fields like cancer research, nevertheless, poorly understood in the context of cardiovascular disease. Epitranscriptomic modifications are shown to regulate the metabolism and function of RNA molecules, which are important for cell functions such as cell proliferation, a key aspect in atherogenesis. As such, epitranscriptomic regulatory mechanisms can serve as novel checkpoints in gene expression during disease development. In this review, we describe examples of the latest research investigating epitranscriptomic modifications, in particular A-to-I editing and the covalent modification N 6 -methyladenosine and their regulatory proteins, in the context of cardiovascular disease. We additionally discuss the potential of these mechanisms as therapeutic targets and novel treatment options.